In vitro Evaluation of Titanium Exfoliation during Simulated Surgical Insertion of Dental Implants - Tanisha Mishra; Bhavna Jha Kukreja; Ruchi Patel; Mahesh Ghadage; Pranita Dalave; Shivani Kumari; Naina Pattnaik; Manish S. Jadhav (Journal of Pharmacy and Bioallied Sciences)
Background: Titanium dental implants are widely used due to their biocompatibility and mechanical properties. However, the potential for titanium particle exfoliation during surgical insertion remains a concern, as it may affect osseointegration and peri-implant health. This study aims to evaluate the extent of titanium exfoliation during simulated surgical insertion of dental implants. Materials and Methods: A total of 30 titanium dental implants were surgically inserted into synthetic bone blocks using a standardized drilling protocol. The procedure was conducted in a controlled laboratory environment to simulate clinical conditions. Titanium particle exfoliation was assessed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) at multiple insertion depths (0 mm, 5 mm, and 10 mm). The quantity of titanium particles was measured and analyzed statistically. Results: The SEM and EDS analyses revealed significant titanium exfoliation at each insertion depth. The mean number of titanium particles detected at 0 mm, 5 mm, and 10 mm depths were 25 ± 5, 45 ± 8, and 60 ± 10 particles per mm2, respectively. There was a statistically significant increase in particle count with increasing depth of insertion (P < 0.01). Conclusion: The findings indicate that titanium exfoliation occurs during the surgical insertion of dental implants and increases with the depth of insertion. This exfoliation could potentially impact peri-implant tissue health and osseointegration. Further clinical studies are necessary to assess the long-term effects of titanium particle exfoliation on implant success.